Analisis Kinerja Belanja Pemerintah daerah Kotamobagu dan Bolaang Mongondow Timur tahun 2009-2012 - Karamoy, Herman; Wokas, Heince (Universitas Sam Ratulangi, 2014)
Budget Realization Report (LRA) which published local governments provide very useful information to assess the financial performance. This study aims to analyze the performance of the Local Government and Bolaang Mongondow Timur danÂ KotamobaguÂ 2009-2012. The analysis showed that both the local government needs to improve the performance of the financial management